A conceptual image-based data glove for computer-human interaction - Fernandes, Leandro Augusto Frata (2008)
Data gloves are devices equipped with sensors that capture the movements of the hand of the user in order to select or manipulate objects in a virtual world. Data gloves were introduced three decades ago and since then have been used in many 3D interaction techniques. However, good data gloves are too expensive and only a few of them can perceive the full set of hand movements. In this paper we describe the design of an image-based data glove (IBDG) prototype suitable for finger sensible applications, like virtual objects manipulation and interaction approaches. The proposed device uses a camera to track visual markers at finger tips, and a software module to compute the position of each finger tip and its joints in real-time. To evaluate our concept, we have built a prototype and tested it with 15 volunteers. We also discuss how to improve the engineering of the prototype, how to turn it into a low cost interaction device, as well as other relevant issues about this original concept.